Períodos de controle e convivência das plantas daninhas na cultura do algodão em diferentes sistemas de cultivo no cerrado brasileiro - Raimondi, Michel Alex (2012)
In search of economic support of the Brazilian cotton, the cotton cultivation system have been changing over the time when you compare what was traditionally made. Recently, dense crop has emerged as one option to increase the crop profitability, especially in spreading performed in "off season" due to the crop cycle reduction and the production costs reductions. Changing in spacing, plant density and sowing time induce a series of changes in growth and cotton development, besides interfering directly in cotton potential competitive with the weeds. Therefore, weed period control in the culture is variable according sowing system adopted. This research had as objective to determine the effects of different cropping systems, regard to spacing and sowing time on the weed interference in cotton yield (Gossypium hirsutum L.) under brazilian savannah conditions. For this, experiments were carried out, where the first (chapter 1) was installed in the summer crop (23/12/2009), with spacing between rows of 0,9 m and plant density of 95,000 ha-1. The second (chapter 2) was installed in 08/01/2010 in the second season after the bean harvest, with spacing between rows of 0,76 m and plant density of 165,000 ha-1. The third experiment (chapter 3) was seeded in the second crop season (04/02/2010), where the area was occupied with soybean, the spacing adopting between rows was of 0.45 m (high density) and the plant density was of 225,000 ha-1. The Bidens pilosa was the main weed in all the systems evaluated. The Period Prior to the interference was longer in the traditional seeding, discussed in experiment 1 (chapter 1). The reduction in spacing and sowing later in cotton resulted in greater initial weed competition. A dense planting of cotton in the off season resulted in lower Period Prior to the interference between the systems evaluated. The Total Period Interference Prevention and the Critical Period for Prevention of Interference was shorter when it took the dense planting of cotton in the off season. The Total Period Interference Prevention and the Critical Period for Prevention of interference were longer in the traditional sowing (chapter 1) in relation to other systems. The luminous flux incident on the culture was the variable that has suffered more similar effects on productivity, on the earliness of the damage suffered by cotton in the early periods of coexistence with the weeds. The dry weight of shoots was the variable related to weeds more important to indicate the periods of control and Weed in cotton. In the system of dense planting of cotton in the off season there is no tolerance for coexistence between the crop and weeds, since productivity was affected significantly in the first days after crop emergence.